A new ipad application for hearing screening in children - Ellaham, Nicolas; Yilma, Yirgu; Jourdan, Guy-Vincent; Bromwich, Matthew (Canadian Acoustics, 2011)
This paper presented a new app developed for the iPad platform to perform CPA tests for screening pre-school children for potential hearing loss. The app is intended for use in free-field environments where access to sound booths and elaborate equipment is not available. Equipment and environment limitations were discussed along with elegant solutions. A means of calibrating the system in two stages is also provided. A prototype of the app has been developed and is presently being tested in trials at the Division of Pediatric Otolaryngology, Head and Neck Surgery at the Children's Hospital of Eastern Ontario.